Utilization of paper mill sludge for removal of cationic textile dyes from aqueous solutions - Yaras, Ali; Arslanoglu, Hasan (Taylor & Francis Inc, 2019)
The present study is concerned usage of paper mill sludge (PMS) as an effective adsorbent to remove the two cationic character dyes (Basic Blue 3 [BB3] and Basic Yellow 28 [BY28]) from aqueous solutions. The surface morphology and some characteristics of PMS were determined by Fouirer Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Brunauer Emmett Teller (BET). The parameters affecting the process - temperature (10-55 degrees C), adsorbent dose (0.5-10 g/l), initial pH (2-10 pH), initial concentration (50-250 mg/l) and contact time (0-24 h) - were examined in the batch adsorption experiments. Maximum adsorption capacities (q(max)) of two dyes at 1 g/l dose and pH value of 7 were also calculated as 89.35 and 79.81, respectively. Adsorption phenomena of BB3 and BY28 cationic dyes onto PMS is controlled by pseudo-second-order model. Thereafter, equilibrium experimental data were applied to Langmuir, Freundlich and Dubinin-Redushkevich (D-R) isotherms, and Langmuir isotherm is the best represent the equilibrium adsorption process for both dyes. The processes occurred by physical adsorption because of calculated activation values (E-a) of BB3 and BY28 dyes were 19.43 and 9.35 kJ/mol, respectively. In addition, based on thermodynamic calculations such as free energy (Delta G degrees), enthalpy (Delta H degrees) and entropy (Delta S degrees), the results clearly demonstrated that the adsorption process were of exothermic and spontaneous nature for both dyes. At the light of obtained findings, it can be stated that PMS can be used effectively in removal of cationic dyes from textile wastewaters and is an alternative to commercial adsorbents due to its low-cost and abundance in the paper industries.
Keywords: Adsorption; paper mill sludge; Basic Blue 3; Basic Yellow 28; isotherm and kinetics